ANALISIS PERUBAHAN KELEMBAGAAN PADA ORGANISASI PELAKSANA PEMBERDAYAAN (Studi Kasus Pada BKAD Kanjuruhan di Kecamatan Wajak Kabupaten Malang) - EKO YUNI PRIHANTONO ; Prof. Munawar Ismail, SE., DEA, Ph.D. Prof. Ahmad Erani Yustika, SE., M.Sc., Ph.D. David Kaluge, SE., MS., M.Ec-Dev., Ph.D
This study aims to analyze the institutional changes, changes_x000D_ determinants, mechanisms and implications of institutional change BKAD_x000D_ Kanjuruhan as the implementing organization empowering the community_x000D_ development activities undertaken during the independence period. _x000D_ This study was conducted with a qualitative approach with a case study_x000D_ method to institutional change that occurred in implementing empowerment_x000D_ organization in the independence period compared with the period of assistance. _x000D_ The results showed that the institutional changes in the organization of_x000D_ implementing empowerment is not just a difference in form, quality, state from_x000D_ time to time of an institution, but also the difference in the quantity of an_x000D_ institutional activity triggered by the common interest of the managers of the_x000D_ organization implementing empowerment. Determinants of institutional change_x000D_ comes from knowledge of actors change, changes in the relative efficiency of_x000D_ development activities, changes in relative prices managed funds, the existence_x000D_ of similar organizations as well as the organization's ability to meet the interests_x000D_ of the managers. Institutional changes took place in the continuum and_x000D_ dynamically adjust the internal and external institutional conditions. Institutional_x000D_ changes that occur due to the desire of the managers of the organization_x000D_ implementing empowerment led to the goal of community empowerment through_x000D_ activities that distributes power to the powerless cannot be achieved. _x000D_ In order for community empowerment program provides benefits to the_x000D_ target is required: mentoring and ongoing incentives for actors, design_x000D_ empowerment programs that empower accommodate the interests of the parties,_x000D_ the parties are empowered, and those who facilitate the empowerment, as well_x000D_ as the certainty of the legal form of the organization implementing empowerment. _x000D_ Key words: institutional changes, implementing organizational empowerment,_x000D_ community empowerment